Two New Cryptic Pristimantis (Anura, Craugastoridae) from the Southern Amazon Basin of Peru with Taxonomic Comments on Pristimantis imitatrix (Duellman, 1978) - Ortega Andrade, H. Mauricio (2021)
Fieldwork in premontane and lowland Amazonian forest (385–1,075 m above sea level) in and around the Amarakaeri Communal Reserve in southeastern Peru led us to describe two new species of the genus Pristimantis. We used integrative evidence from several external morphological characters, morphometric and molecular data, geographic distributions, and multivariate analyses to support the identification of these new species. Pristimantis gagliardi sp. nov. is characterized by lacking a visible tympanic annulus and membrane on skin, having basal webbing between toes, yellow blotches in groin and hidden surfaces of shanks, W-shaped scapular mark, snout subacuminate bearing a very small papilla at tip of snout, and snout–vent length (SVL) = 17.7–21.3 mm in adult males and SVL = 26.7–29.2 mm in females. Pristimantis okmoi sp. nov. is characterized by having a visible tympanic annulus and membrane on skin, basal webbing between toes, yellow blotches in groin and hidden surfaces of shanks, W-shaped scapular mark, snout rounded with small rostral papilla, and SVL = 13.63–17.04 mm in adult males; females unknown. Both species were initially misidentified as P. carvalhoi or P. imitatrix. Additionally, we provide new morphological and phylogenetic data on adult specimens of Pristimantis imitatrix, a rare Amazonian species described based on a single subadult female.